LIBERALISASI KEUANGAN DAN PENGARUHNYA TERHADAP NILAI Q-TOBIN SEKTOR INDUSTRI DASAR DAN KIMIA DAN PERBANKAN - Andati, Trias; Siregar, Hermanto; M. Sinaga, Bonar; Azam Achsani, Noer (Jurnal Manajemen dan Agribisnis, 2012)
This research attempts to analyze the effect of financial liberalization to Q-Tobin ratio of Basic and Chemical industry and Banking sectors. Using annual data of 52 listed company’s financial report from 2002 to 2009, the results show that the financial liberalization variables i.e. Foreign Direct Investment (FDI) and Investment Portfolio has negative effect on Q-Tobin of Basic and Chemical Industry and Banking sectors. The increase of the financial deepening variables has positive effect on Q-Tobin of Basic and Chemical Industry and Banking sectors. SBI (Sertifikat Bank Indonesia) and Money Supply has negative impact on Q-Tobin, while loan interest rates has positive impact on both sectors. The average of net fixed asset investment of two sectors has the same pattern of Q-Tobin values, and increased from 2002 to 2009, while at the year of 2008, Q-Tobin of all sectors experienced decreasing due to financial crisis. Furthermore, there should be a corporate financial performance indicator such as leverage ratio, to prevent short term investment of FDI. Capital Market’s regulation, should be considerate a sectoral policy in portfolio investment, to prevent from financial global crisis. Corporation of two sectors could give more attention on capital structure while analyzing the company’s investment decision. Keywords: Q-Tobin Ratio, Financial Liberalization, Investment, Panel Data